Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine which equations are equivalent to the given formula [tex]\( y = a(x - h)^2 + k \)[/tex], let's analyze each option step-by-step:
### Option A: [tex]\( h = x - \sqrt{\left(\frac{y - k}{a}\right)} \)[/tex]
Starting with the formula:
[tex]\[ y = a(x - h)^2 + k \][/tex]
We need to solve this for [tex]\( h \)[/tex].
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x - h)^2 \][/tex]
2. Divide both sides by [tex]\( a \)[/tex]:
[tex]\[ \frac{y - k}{a} = (x - h)^2 \][/tex]
3. Take the square root of both sides:
[tex]\[ \sqrt{\frac{y - k}{a}} = x - h \][/tex]
4. Solve for [tex]\( h \)[/tex]:
[tex]\[ h = x - \sqrt{\frac{y - k}{a}} \][/tex]
Thus, Option A is correct.
### Option B: [tex]\( a = \frac{y - k}{(x - h)^2} \)[/tex]
Starting with the formula:
[tex]\[ y = a(x - h)^2 + k \][/tex]
We need to solve this for [tex]\( a \)[/tex].
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x - h)^2 \][/tex]
2. Divide both sides by [tex]\( (x - h)^2 \)[/tex]:
[tex]\[ a = \frac{y - k}{(x - h)^2} \][/tex]
Thus, Option B is correct.
### Option C: [tex]\( k = y +(x - h)^2 \)[/tex]
Starting with the formula:
[tex]\[ y = a(x - h)^2 + k \][/tex]
We need to solve this for [tex]\( k \)[/tex].
1. Subtract [tex]\( a(x - h)^2 \)[/tex] from both sides:
[tex]\[ y - a(x - h)^2 = k \][/tex]
So,
[tex]\[ k = y - a(x - h)^2 \][/tex]
Option C states [tex]\( k = y + (x - h)^2 \)[/tex], which is incorrect according to our solution.
Thus, Option C is incorrect.
### Option D: [tex]\( x = \pm \sqrt{\frac{y - k}{a}} + h \)[/tex]
Starting with the formula:
[tex]\[ y = a(x - h)^2 + k \][/tex]
We need to solve this for [tex]\( x \)[/tex].
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x - h)^2 \][/tex]
2. Divide both sides by [tex]\( a \)[/tex]:
[tex]\[ \frac{y - k}{a} = (x - h)^2 \][/tex]
3. Take the square root of both sides:
[tex]\[ \sqrt{\frac{y - k}{a}} = x - h \][/tex]
or
[tex]\[ -\sqrt{\frac{y - k}{a}} = x - h \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \sqrt{\frac{y - k}{a}} + h \][/tex]
or
[tex]\[ x = -\sqrt{\frac{y - k}{a}} + h \][/tex]
Thus, Option D is correct.
### Conclusion
The correct options are:
- Option A: [tex]\( h = x - \sqrt{\left(\frac{y - k}{a}\right)} \)[/tex]
- Option B: [tex]\( a = \frac{y - k}{(x - h)^2} \)[/tex]
- Option D: [tex]\( x = \pm \sqrt{\left(\frac{y - k}{a}\right)} + h \)[/tex]
So, the correct answer is:
[tex]\[ \text{Options: } [1, 2, 4] \][/tex]
### Option A: [tex]\( h = x - \sqrt{\left(\frac{y - k}{a}\right)} \)[/tex]
Starting with the formula:
[tex]\[ y = a(x - h)^2 + k \][/tex]
We need to solve this for [tex]\( h \)[/tex].
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x - h)^2 \][/tex]
2. Divide both sides by [tex]\( a \)[/tex]:
[tex]\[ \frac{y - k}{a} = (x - h)^2 \][/tex]
3. Take the square root of both sides:
[tex]\[ \sqrt{\frac{y - k}{a}} = x - h \][/tex]
4. Solve for [tex]\( h \)[/tex]:
[tex]\[ h = x - \sqrt{\frac{y - k}{a}} \][/tex]
Thus, Option A is correct.
### Option B: [tex]\( a = \frac{y - k}{(x - h)^2} \)[/tex]
Starting with the formula:
[tex]\[ y = a(x - h)^2 + k \][/tex]
We need to solve this for [tex]\( a \)[/tex].
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x - h)^2 \][/tex]
2. Divide both sides by [tex]\( (x - h)^2 \)[/tex]:
[tex]\[ a = \frac{y - k}{(x - h)^2} \][/tex]
Thus, Option B is correct.
### Option C: [tex]\( k = y +(x - h)^2 \)[/tex]
Starting with the formula:
[tex]\[ y = a(x - h)^2 + k \][/tex]
We need to solve this for [tex]\( k \)[/tex].
1. Subtract [tex]\( a(x - h)^2 \)[/tex] from both sides:
[tex]\[ y - a(x - h)^2 = k \][/tex]
So,
[tex]\[ k = y - a(x - h)^2 \][/tex]
Option C states [tex]\( k = y + (x - h)^2 \)[/tex], which is incorrect according to our solution.
Thus, Option C is incorrect.
### Option D: [tex]\( x = \pm \sqrt{\frac{y - k}{a}} + h \)[/tex]
Starting with the formula:
[tex]\[ y = a(x - h)^2 + k \][/tex]
We need to solve this for [tex]\( x \)[/tex].
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x - h)^2 \][/tex]
2. Divide both sides by [tex]\( a \)[/tex]:
[tex]\[ \frac{y - k}{a} = (x - h)^2 \][/tex]
3. Take the square root of both sides:
[tex]\[ \sqrt{\frac{y - k}{a}} = x - h \][/tex]
or
[tex]\[ -\sqrt{\frac{y - k}{a}} = x - h \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \sqrt{\frac{y - k}{a}} + h \][/tex]
or
[tex]\[ x = -\sqrt{\frac{y - k}{a}} + h \][/tex]
Thus, Option D is correct.
### Conclusion
The correct options are:
- Option A: [tex]\( h = x - \sqrt{\left(\frac{y - k}{a}\right)} \)[/tex]
- Option B: [tex]\( a = \frac{y - k}{(x - h)^2} \)[/tex]
- Option D: [tex]\( x = \pm \sqrt{\left(\frac{y - k}{a}\right)} + h \)[/tex]
So, the correct answer is:
[tex]\[ \text{Options: } [1, 2, 4] \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.